(untitled) (Castilla. Estudios de Literatura, 2016)
Considering the polemic critic caused by Cervantes and religions, and the increase in the number of studies about the otherness in cultural studies, in this work we will analyse the treatment of Muslims in several works by Miguel de Cervantes, through an intratextual approximation. In particular, we will study the different variations of two prominent themes in Cervantes’ production: the Turkish invasions of the Spanish’s coasts (present in La Galatea and in El Persiles) and the renegados’ problem, Christians who renounced to their faith to be part of the Mohammedan pirates’ army. In In this way, we want to observe if there is any possible evolution of the thought among the years in Cervantes’ writings, or if it is possible to find any constant about the Muslim theme.